Impact of Entrepreneurial Characteristics on the Performance of Small Scale Enterprises in Vavuniya - Kengatharan, L.; Kodithuwakku, S.S. (2010 Vavuniya Campus Annual Reasearch Session, 2010)
Thissnrdyexaminestheimpactofentrepreneurial.characteristicsontheperformanceofsmall. scaleorterprisesintheoi,ui.totVavuniya.Thisiswithaviewtoevaluatethoentepreneurial charactpristicsimpactonbu,in.,,performanceandfindoutwhichentreproneurialcharacteristics ar€mostimportanttoinfluenceonbusinessperforrnance'Entrepreneurialcharacteristicswere conceptualizedwithinthecombinationsofachievernentcompctenoies,planningcompetenciesand powercompetoncies.Primarydata,throughquestionnairesurveywith,directpersonalinrcniew teohniquesworecollectedfromthe56sampleofsmall.scaleentrcproT:r:1|ouefunctioningin thedistrictofVavuniya.Datawereanalyzedusingdescrtptiveandinferentialstatistics.Nso, conelation analysiq and regresioL analysis were caried out to examllethe relationship between contextual variabres and business performance ** ,nu aid of statistical Packages for social Scionces(SPSS).Thisstudyhypothesizedthatentrepreneurialcharacteristic,asacompositeas well as its dimenqions donlt have relationship with business pt'folmantt' Findings of the result demonstratedttratentropreneurialcharactuisticshavepositiveimpactonbusinessperfotmance' Among the three salient competencies' 'plannin' 'oti"tn"ts are the most important factor to influence on business porformance'
Keywords: Entrepreneurial characteristics; Business performance; Small- scale enterprises